2018
DOI: 10.37119/ojs2018.v24i1.348
|View full text |Cite
|
Sign up to set email alerts
|

The Flipped Classroom: High School Student Engagement Through 21st Century Learning

Abstract: The purpose of this qualitative study is to document the experiences of students who participated in a flipped classroom during a Grade 11 Modern World History and a Grade 11 Biology course. An abridged literature review revealed the flipped classroom provides enriched opportunities for collaborative learning and for greater teacher-student interaction; however, during the homework phase, some students are not equipped to be independent learners. For this action research project, we collected data from 48 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Another study by Strayer found that students were more receptive to cooperative learning after adopting the flipped classroom style to study statistics (Strayer, 2012). The flipped classroom promotes cooperative learning and teacher-student interaction (Avery et al, 2018).…”
Section: Flipped Learning and Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Strayer found that students were more receptive to cooperative learning after adopting the flipped classroom style to study statistics (Strayer, 2012). The flipped classroom promotes cooperative learning and teacher-student interaction (Avery et al, 2018).…”
Section: Flipped Learning and Student Achievementmentioning
confidence: 99%
“…In addition to subject areas like Math, Science, Social Studies, English Language Arts, etc., more research on flipped classrooms at the elementary, middle, and high school levels has to be considered. According to studies, there is very little information on flipped classrooms at all grade levels (Alpay & Gulati, 2010;Avery et al, 2018;Bergman & Sams, 2012a;Flumerfelt & Green, 2013;Fulton, 2012;Gough et al, 2017;Heilesen, 2010;Hew, 2009;Johnson & Renner, 2012;Milman, 2012;Redekopp & Ragusa, 2013). It is essential to understand how flipped classroom characteristics may vary across grade levels and how those characteristics may relate to satisfaction across grade levels.…”
Section: Future Researchmentioning
confidence: 99%
“…Kahu and Nelson's (2017) critical review of student engagement in the educational interface found that with high self-efficacy, there is an increase of student engagement and success and as an equal exchange, increased engagement, which in turn increases self-efficacy. In their action research, Avery et al (2018) administered a questionnaire among students and found that the students were generally interested in flipped classroom and admitted that they enjoyed learning.…”
Section: Flipped Classroommentioning
confidence: 99%
“…Thus, teachers today confront the greatest challenge in satisfying these pupils' diverse learning demands (Kaur, 2017). As a means of getting more students engaged and promoting student-centred learning, the flipped classroom is an example of a pedagogy that is compatible with 21st-century learning styles (Avery et al, 2018). However, from the teacher's point of view, active participation is not only required of students alone but also parents, stakeholders and teachers in order to make flipped classroom a success (Mitsiou, 2019).…”
Section: Teachers' Experiences and Challenges With Flipped Classroommentioning
confidence: 99%
“…According to (Angadi et al, 2019), flipped classroom education enables students to encounter new features outside of class rather than typical review tasks. 'The flipped classroom is an example of pedagogy related to teaching and learning processes of twenty-first-century learners,' says the author (Avery & Huggan, 2018).…”
Section: Introductionmentioning
confidence: 99%